Unconstrained Impedance Control Using a Compact Series Elastic Actuator - Sensinger, Jonathon W.; Weir, Richard F.ff (2006 2nd IEEE/ASME International Conference on Mechatronics and Embedded Systems and Applications, 2006)
Series elastic actuators offer high fidelity force control with inherent low impedance above their controllable frequency bandwidth. As a result they well suited for interaction with humans, in which safety is paramount. Their high force fidelity suggests that they may be a suitable for impedance control, in which the interaction between motion and force is controlled. The authors model the unconstrained actuator, and perform tests to evaluate the ability of series elastic actuators to mimic different stiffness. Series elastic actuators are found to be adequate for unconstrained impedance control at input frequencies below 3 Hz